(untitled) (International Journal of Engineering Management Science, 2022)
The growth of society is significantly influenced by the judiciary. Even while interpretation does not primarily deal with creating laws, the judiciary might use this strategy to give the laws that already exist a new perspective and effect the required social changes. The foundation of a parliamentary democratic system of government is an independent judiciary. In a parliamentary system, an independent judiciary bears a vital role. The adage that "all power corrupts" is overused. The unification of the legislative, executive, and judicial departments into a single entity—the Sovereign—led to despotism. As a result, the mediaeval monarchy had to deal with the rise of the common will. The monarchies of England and France were not only subjected to, but also defeated by, popular revolutions that successfully transferred sovereignty to the people. The idea that the three arms of government should remain separate from one another was another issue that these revolutions brought to light. It was intended for the creation, management, and application of laws to be housed under three distinct and autonomous entities. Three separate but interdependent branches of the same state emerged to control the State’s will, its execution, and the assessment of the first branch’s genuine character and the second branch’s propriety. Therefore, the idea that led to the growth of democracy primarily focuses on representative government and the functional distribution of its authority. According to Henry Sidgewich, the role of the government should be "divided under three main heads, as Legislature, Executive and Judicial, each division being allotted to a separately constituted organ." This is in line with the present definition of statecraft.